The oldest gospel and the formation of the canonical gospels - Klinghardt, Matthias (Biblical tools and studies, 2021)
"The Gospel that was part of Marcion's collection in the first half of the 2nd century is the oldest of all Gospels. The author presents a meticulous reconstruction and argues that all canonical Gospels are dependent on this Gospel. This sheds new light on the formation and tradition history of the gospels, contributes new insights on the history of the New Testament text and textual criticism, and has significant consequences for how to assess the formation of the canonical edition of the New Testament and the history of earliest Christianity in general. Part I contains the methodological foundation, substantiating the hypothesis that canonical Luke is a revised edition of this oldest Gospel. On this ground, a model of the Gospels' tradition history is developed. A detailed epilogue comments on recent research on and reconstructions of Marcion's Gospel and analyzes the methodological differences of these approaches."--Part I, back cover